(untitled) (MAUSAM, 1978)
In a study of the planetary-scale vorticity budget of the northern summer monsoon, Holton and Colton (1973) found that a strong vorticity sink is needed to balance the generation by horizontal divergence at 200 mb. In this work we use numerical experiments to examine the hypothesis that the fluctuation of the divergence forcing as observed by several studies serves as this sink. A 3-1evel numerical model is used with the thermal forcing specified by the horizontal divergence distribution observed by Krishnamurti (1971). Two experiments are carried out, one with heating steady in time and the other fluctuating in time with a period of 10 days. The time-mean fields of the quasi-steady state solution in both experiments show a significant westward phase shirt of the Tibetan high, thus the fluctuation of heating cannot be a sufficient sink. On the other hand, the positions of the simulated tropical upper tropospheric troughs agree quite well with those observed. This suggests that damping due to cumulus transport is more likely to account for the vorticity sink. Transient wave activities are also found at the upper level in both experiments. They appear to be drawing energy from the planetary-scale flow and could serve as a vorticity sink. These waves are most active in the fluctuating heating case, suggesting that local barotropic instability at upper levels may be more important than that implied by the time-meanwind.